Just policy? An ethical analysis of early intervention policy guidance - Mortimer, R; McKeown, A; Singh, I (Taylor and Francis, 2018)
Early intervention (EI) aims to identify children or families at risk of poor health, and take preventative measures at an early stage, when intervention is more likely to succeed. EI is concerned with the just distribution of ‘life chances’, so that all children are given fair opportunity to realise their potential and lead a good life; EI policy design, therefore, invokes ethical questions about the balance of responsibilities between the State, society, and individuals in addressing inequalities. We analyse a corpus of EI policy guidance to investigate explicit and implicit ethical arguments about who should be held morally responsible for safeguarding child health and wellbeing. We examine the implications of these claims and explore what it would mean to put the proposed policies into practice. We conclude with some remarks about the useful role that philosophical analysis can play in EI policy development.